Saving and After-Tax Rates of Return - Friend, Irwin; Hasbrouck, Joel (The Review of Economics and Statistics, 1983)
IN recent years number of economists have found, or taken for granted, substantial positive interest elasticity of private saving, and several have concluded that the taxation of property income has played major role in depressing and investment and therefore economic welfare.' Thus, probably the most quoted of these studies, by Michael Boskin (1978), finds that a variety of functional forms, estimation methods and definitions of the real-after-tax rate of return invariably lead to the conclusion of substantial positive interest elasticity of private saving (p. 3). As consequence he states, current tax treatment of income from capital significantly retards capital accumulation... Rough estimates of the lost welfare $50 billion per year... . The most recent of these studies, by Lawrence Summers (1981), uses the Boskin empirical results to check corresponding findings based on assumed values of the relevant parameters in life-cycle model of aggregate behavior. Summers raises the ante in his estimate of the welfare gain associated with the elimination of capital income taxation, claiming it would exceed $150 billion annually, and noting that this conclusion rests on high positive interest elasticity of (p. 533). Summers notes that his larger interest rate effect reflects his additional allowance for wealth changes. Since these findings on interest elasticity are inconsistent with earlier studies,2 and have received widespread attention by political activists, it is important to determine how much confidence can be placed in the underlying analysis. This paper will demonstrate that there is little scientific justification for the recent literature purporting to show strong positive interest elasticity of saving, so that government tax policies predicated on such behavior rest on dubious foundation. The evidence to be presented will indicate that at the present stage of knowledge, we have no sound basis for alleging either strong positive or negative after-tax rate of return effect on saving. The only prior published examination of these recent potentially important findings of strong positive interest elasticity of private has been brief reference to the Boskin results in paper by Howrey and Hymans (1978), which was largely devoted to an analysis of what the authors call personal cash or loanable funds rather than private saving. These authors report that the significance of Boskin's results is sensitive to estimation period, inclusion of lagged unemployment, and use of alternative interest rate variables. They do not report the results of the alternative estimations, however, nor do they present consistent instrumental variable estimations, despite the fact that the latter provide Boskin with what he considers to be his best results. In this paper in striking contrast to the Boskin analysis, we show that using the best available proxies for the relevant interest rate variables (real expected after-tax rates of return, estimated both on an ex ante and on an ex post basis), the estimated interest elasticity of household and private is generally found to be either statistically insignificant or significantly negative and only rarely significantly positive, with the result depending on the specific interest rate series, period and consumption function used. Nor is this finding altered when the single equation estimation of this or consumption function is replaced by an instrumental variable, consistent estimation. As result, there does not seem to be much basis to Boskin's or Summers' strong criticism of the earlier literature which generally concluded that there was Received for publication May 14, 1982. Revision accepted for publication November 23, 1982. *University of Pennsylvania. See Boskin (1978), Gylfason (1981) and Summers (1981). 2 See the consumption function in either the Wharton model (The Wharton Mark IV Quarterly Econometric Model, Philadelphia, 1977 and updates) or the MPS Model (The Quarterly Econometric Model, Board of Governors of the Federal Reserve System, 1978 and updates).